Circulating Reelin promotes inflammation and modulates disease activity in acute and long COVID-19 cases - Calvier, Laurent; Drelich, Aleksandra; Hsu, Jason; Tseng, Chien-Te; Mina, Yair; Nath, Avindra; Kounnas, Maria Z.; Herz, Joachim (Frontiers in Immunology, 2023)
Thromboembolic complications and excessive inflammation are frequent in severe Covid-19, potentially leading to long Covid. In non-Covid studies, we and others demonstrated that circulating Reelin promotes leukocyte infiltration and thrombosis. Thus, we hypothesized that Reelin participates in endothelial dysfunction and hyperinflammation during Covid-19. We showed that Reelin was increased in Covid-19 patients and correlated with the disease activity. In the severe Covid-19 group, we observed a hyperinflammatory state, as judged by increased concentration of cytokines (IL-1α, IL-4, IL-6, IL-10 and IL-17A), chemokines (IP-10 and MIP-1β), and adhesion markers (E-selectin and ICAM-1). Reelin level was correlated with IL-1α, IL-4, IP-10, MIP-1β, and ICAM-1, suggesting a specific role for Reelin in Covid-19 progression. Furthermore, Reelin and all of the inflammatory markers aforementioned returned to normal in a long Covid cohort, showing that the hyperinflammatory state was resolved. Finally, we tested Reelin inhibition with the anti-Reelin antibody CR-50 in hACE2 transgenic mice infected with SARS-CoV-2. CR-50 prophylactic treatment decreased mortality and disease severity in this model. These results demonstrate a direct proinflammatory function for Reelin in Covid-19 and identify it as a drug target. This work opens translational clinical applications in severe SARS-CoV-2 infection and beyond in auto-inflammatory diseases.